501. Interferon-gamma Release Assays for Diagnosis of Latent TB Infection in Chronic Kidney Disease and Dialysis Patients. (15th December 2022) - Hayuk, Pattorn; Boongird, Sarinya; Pornsuriyasak, Prapaporn; Bruminhent, Jackrapong
Abstract: Background: Patients with chronic kidney disease (CKD), especially end-stage kidney disease (ESKD), are at risk of developing tuberculosis (TB). Due to their relatively immunosuppresses condition, reactivation from latent TB infection (LTBI) is the core pathogenesis in these populations. However, the prevalence of LTBI among Thai CKD patients, assessed by a high sensitivity and specificity test such as interferon-gamma release assay (IGRA), has never been thoroughly explored. We aimed to investigate the prevalence and predictors for LTBI among Thai CKD patients, including ESKD individuals receiving renal replacement therapy (RRT) either by hemodialysis (HD) or peritoneal dialysis (PD). Methods: All CKD patients who underwent an investigation for LTBI status at Ramathibodi hospital were prospectively recruited from September 2020 to November 2021 and retrospectively reviewed from December 2020 to November 2021. Those with positive or borderline IGRA results using T SPOT®.TB without clinical or radiological findings compatible with active TB was diagnosed with LTBI. The LTBI prevalence was determined by CKD staging and type of dialysis. Predictors for LTBI were assessed by logistic regression analysis. Results: A total of 199 CKD patients were enrolled; 102 prospectively and 97 retrospectively. There were 173 evaluable patients included with a mean (SD) age of 53 (16) years, and 44% were male. Of those, 95 (55%) had ESKD and maintained on RRT. Overall, 39 (22.5%) CKD patients had LTBI with the prevalence of 25%, 12.5%, 25%, 25% and 24.2% in those with CKD stage 1, 2, 3a, 3b and ESKD, respectively ( p =0.89). Among ESKD patients, those who were maintained on HD had a higher proportion of LTBI than those on PD (28.9% vs. 5.3%, p =0.03). In multivariate analysis, drinking alcohol was significantly associated with LTBI (OR 8.51; [95%CI 1.24-58.38]; p =0.029), and HD therapy was marginally associated with LTBI (OR 8.14; [95%CI 0.95-69.91]; p =0.056) among ESKD patients. Conclusion: In TB endemic settings, one-fifth of patients with CKD and a quarter of ESKD patients could carry LTBI status. Alcohol consumption and HD therapy could better identify high-risk ESKD patients and potentially screen for LBTI. Disclosures: All Authors : No reported disclosures.